Comercio Electrónico, La Evolución De Un Comercio Internacional Más Ágil Y Avanzado (2023)
The incorporation of e-commerce in international trade has revolutionized the way companies conduct transactions and sell products worldwide. Thanks to digitization and information technologies, companies can reach customers worldwide more easily and efficiently, increasing the reach of international trade.